2008
DOI: 10.1176/appi.ps.59.12.1406
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Restraint and Seclusion Through Collaborative Problem Solving: A Five-Year Prospective Inpatient Study

Abstract: CPS is a promising approach to reduce seclusion and restraint use in a child psychiatric inpatient setting. Future research and replication efforts are warranted to test its effectiveness in other restrictive settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…After applying the inclusion criteria, 13 publications were excluded: 6 did not meet the time-frame [2,10,20,23,31,35]; 2 papers did not report original research [8,13] and 5 did not present prevalence data for seclusion or restraint use [8,19,28,26,33] Four of the 7 included studies had a pre-intervention/post-intervention design (n=1,302) [6,17,18,21], two were descriptive studies (n=590) [9,15], and the last one was a cross-sectional survey (n=504) [32] (Table 1). …”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After applying the inclusion criteria, 13 publications were excluded: 6 did not meet the time-frame [2,10,20,23,31,35]; 2 papers did not report original research [8,13] and 5 did not present prevalence data for seclusion or restraint use [8,19,28,26,33] Four of the 7 included studies had a pre-intervention/post-intervention design (n=1,302) [6,17,18,21], two were descriptive studies (n=590) [9,15], and the last one was a cross-sectional survey (n=504) [32] (Table 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…The most consistent findings were aggression and/or violent behaviour, both past and current, suicidal behaviour, more severe psychopathology [6,15,21,32] and non-White ethnicity in some US studies [9,21]. In the study by Donovan et al, both emergency admissions and younger age were associated with higher SRU rates, this finding contrasts with those by Martin et al who found higher restraint use in older patients [9,21]. One study found out-ofhome placement to be a risk-factor [32], while another study identified poorer family functioning [15].…”
Section: Correlates and Risk Factorsmentioning
confidence: 89%
See 2 more Smart Citations
“…There are complex legal and ethical issues associated with their use (Moylan, 2009), as well as the potential for physical and psychological harm to patients (Martin, Krieg, Esposito, Stubbe, & Cardona, 2008). Consequently, there has been a global effort to reduce the use of restrictive measures in all mental health settings.…”
Section: Introductionmentioning
confidence: 99%